Linking composition of extracellular polymeric substances (EPS) to the physical structure and hydraulic resistance of membrane biofilms. (1st April 2018) - Desmond, Peter; Best, James P.; Morgenroth, Eberhard; Derlon, Nicolas
Abstract: The effect of extracellular polymeric substances (EPS) on the meso-scale physical structure and hydraulic resistance of membrane biofilms during gravity driven membrane (GDM) filtration was investigated. Biofilms were developed on the surface of ultrafiltration membranes during dead-end filtration at ultra-low pressure (70 mbar). Biofilm EPS composition (total protein, polysaccharide and eDNA) was manipulated by growing biofilms under contrasting nutrient conditions. Nutrient conditions consisted of (i) a nutrient enriched condition with a nutrient ratio of 100:30:10 (C: N: P), (ii) a phosphorus limitation (C: N: P ratio: 100:30:0), and (iii) a nitrogen limitation (C: N: P ratio: 100:0:10). The structure of the biofilm was characterised at meso-scale using Optical Coherence Tomography (OCT). Biofilm composition was analysed with respect to total organic carbon, total cellular mass and extracellular concentrations of proteins, polysaccharides, and eDNA. 2D-confocal Raman mapping was used to characterise the functional group composition and micro-scale distribution of the biofilms EPS. Our study reveals that the composition of the EPS matrix can determine the meso-scale physical structure of membrane biofilms and in turn its hydraulic resistance. Biofilms grown under P limiting conditions were characterised by dense and homogeneous physical structures with high concentrations of polysaccharides and eDNA. Biofilm grown under nutrient enriched or N limiting conditions were characterised by heterogeneous physical structures with lower concentrations of polysaccharides and eDNA. For P limiting biofilms, 2D-confocal Raman microscopy revealed a homogeneous spatial distribution of anionic functional groups in homogeneous biofilm structures with higher polysaccharide and eDNA concentrations. This study links EPS composition, physical structure and hydraulic resistance of membrane biofilms, with practical relevance for the hydraulic performances of GDM ultrafiltration. Graphical abstract: Image 1 Highlights: Hydraulic resistance of biofilms formed during GDM filtration was studied. Influent composition determined EPS chemical composition. Resulting EPS compositions were linked to distinct physical structures. Hydraulic resistance was dependent on biofilm thickness and density.